Peer violence in primary and secondary schools in the Maribor Police Directorate area - Krope, Srečko (Varstvoslovje, 2026)
Purpose: The article examines peer violence in primary and secondary schools located in the area of the Maribor Police Directorate. Focus is given to identifying the prevalence, forms and perceptions of peer violence, along with analysing the way pupils and students evaluate the role of schools and the police in addressing and preventing such violence. The school environment is shown to be the main setting in which peer violence occurs and also where preventive measures can be most effective. Methods: The study was conducted using a quantitative survey method. The sample comprised pupils from the final three grades of primary schools and students from secondary schools in the area of the Maribor Police Directorate. The collected data were analysed using basic descriptive statistical methods, which provide insights into the frequency of peer violence, perceptions of violence, and how the participants viewed the way it is managed in the school environment. Findings: Peer violence is relatively common in the school environment. Verbal violence was identified as the most frequent form, followed by physical and online violence, with multiple forms often being simultaneous. Peer violence was shown to most frequently occur among classmates, whereas pupils and students generally do not directly become involved when witnessing violence, and instead report the incident to an adult or move away from the situation. In addition, a reduced sense of safety in schools was revealed, and a critical assessment made of how effective school-based measures are at preventing peer violence. Research limitations/implications: The study is based on a non-probability sample and online data collection, which limits the generalisability of the findings to a broader population. Nevertheless, the sample size allows for a robust analysis of patterns in pupils’ and students’ views on and attitudes concerning peer violence in the regional context under study. Practical implications: The findings increase understanding of peer violence in primary and secondary schools in the Maribor Police Directorate area. The results may be compared with findings for other regions in Slovenia and could provide a basis for making preventive activities carried out by schools and the police more effective. Originality/value: The article presents an empirical study on peer violence in the school environment in which the responses of pupils and students, together with the role of institutions, was examined with respect to responding to peer violence. The findings contribute to the field of security studies by expanding knowledge concerning effective approaches to protecting children and adolescents from peer violence.
Keywords: child protection; medvrstniško nasilje; peer violence; police; policija; prevention; preventiva; school environment; šolsko okolje; varstvo otrok